Resilience and supporting people living with dementia during the time of COVID-19; A qualitative study. (January 2022) - Hanna, Kerry; Giebel, Clarissa; Butchard, Sarah; Tetlow, Hilary; Ward, Kym; Shenton, Justine; Cannon, Jacqueline; Komuravelli, Aravind; Gaughan, Anna; Eley, Ruth; Rogers, Carol; Rajagopal, Manoj; et al.
Objectives: To explore the different factors of resilience for people living with dementia and unpaid carers, in response to sudden changes in care and lifestyle during the COVID-19 pandemic. Methods: Unpaid carers and people living with dementia were offered telephone interviews in April 2020 to discuss their experiences since the COVID-19 pandemic. Participants were asked about the benefits and challenges of accessing dementia support, as well as coping, symptoms, strategies and impacts. Each transcript was analysed using inductive and deductive thematic analysis by two researchers. Findings: Semi-structured interviews from 50 participants ( n = 42 unpaid carers and n = 8 people living with dementia) reported protective and risk factors of resilience concerning (1) communication, (2) adaptations, (3) support networks and (4) lifestyle factors and coping mechanisms. Conclusions: Resilience factors considered both organisational factors for external support, along with individual coping mechanisms. Organisations and social support services should consider resilience factors in future service planning, to better support people living with dementia, or caring someone living with dementia, during times of great stress. The ecological model of resilience established from this research refers to resilience during times of unexpected change in the COVID-19 pandemic; however, it could be considered relevant in other periods of high stress within this cohort.